PRP8A and PRP8B spliceosome subunits act coordinately to control pollen tube attraction in Arabidopsis thaliana - Kulichová, Katarína; Kumar, Vinod; Steinbachová, Lenka; Klodová, Božena; Timofejeva, Ljudmilla; Juříček, Miloslav; Honys, David; Hafidh, Said S (Development (Cambridge, England), 2020)
Precise guided pollen tube growth by the female gametophyte is a prerequisite for successful sexual reproduction in flowering plants. Cysteine-rich proteins (CRPs) secreted from the embryo sac are known pollen tube attractants perceived by pollen tube receptor-like kinases. How pre-mRNA splicing facilitates this cell-to-cell communication is not understood. Here, we report a novel function of Pre-mRNA PROCESSING factor 8 paralogs, PRP8A and PRP8B, as regulators of pollen tube attraction. Double mutant prp8a prp8b ovules cannot attract pollen tubes, and prp8a prp8b pollen tubes fail to sense the ovule's attraction signals. Only 3% of ovule-expressed genes were misregulated in prp8a prp8b Combination of RNA sequencing and the MYB98/LURE1.2-YFP reporter revealed that the expression of MYB98, LUREs and 49 other CRPs were downregulated, suggesting loss of synergid cell fate. Differential exon usage and intron retention analysis revealed autoregulation of PPR8A/PRP8B splicing. In vivo, PRP8A co-immunoprecipitates with splicing enhancer AtSF3A1, suggesting involvement of PRP8A in 3'-splice site selection. Our data hint that the PRP8A/PRP8B module exhibits spliceosome autoregulation to facilitate pollen tube attraction via transcriptional regulation of MYB98, CRPs and LURE pollen tube attractants.
Keywords: Cysteine-rich proteins; proteiny huseníčku; Post-transcriptional regulation; Arabidopsis; fluorescenční mikroskopie; Sexual reproduction; Pre-mRNA PROCESSING factor 8; sestřihové faktory; RNA Splice Sites; Amino Acid Sequence; Arabidopsis Proteins; pylová láčka; RNA Splicing Factors; Protein Subunits; sekvenční seřazení; regulace genové exprese u rostlin; Spliceosomes; podjednotky proteinů; Splicing; spliceozomy; Plants, Genetically Modified; Pollen Tube; Cell-to-cell signaling; Microscopy, Fluorescence; Transcription Factors; mutageneze; Gene Expression Regulation, Plant; transkripční faktory; RNA-Binding Proteins; Pollen tube attraction and reception; místa sestřihu RNA; sekvence aminokyselin; geneticky modifikované rostliny; Mutagenesis; proteiny vázající RNA; Sequence Alignment